THE OLIVEIRA FULL FUNCTIONAL RECOVERY METHOD (MORFT®) AND ITS EFFECTIVENESS RESULTS IN THE RECOVERY OF PATIENTS WITH LUMBAR DISC HERNIATION (Fiep Bulletin - online, 2014)
The Oliveira Full Functional Recovery Method (MORFT®) uses preventive, compensatory and corrective exercises specially developed for the method. For the last 28 years, it has been used in public health to assist in the recovery of a large population group affected by lower back pain. Lower back pain is one of the leading causes of lost work time around the world, with a significant impact both on the individual and the national economy. The goal of this study was to observe the effect and results of MORFT® exercises and their established stretching times in the recovery of patients with lumbar disc herniation. This study was performed for 10, 20, 30 and 40 sessions on a sample of 44 patients diagnosed using NMR and reported pain symptoms. The material used consisted of the Morftaco® (a device developed and patented for practicing the MORFT®), couches, chairs, timers and mats. The Numeric Pain Scale (NPS) was used to quantify performance the results in the recovery of functional capacity. It was found that 95.45% of the sample was completely symptom-free by the end of the treatment period, while 4.55% had symptoms scoring less than 1 out of 10 on the NPS. Thus, MORFT® is an effective conservative therapy tool for the recovery of patients with lumbar disc herniation.
Keywords: Lumbar disc herniation; Stretching; MORFT